Different approaches to the pursuit of internationalization by Italian SMEs. Issue 2 (19th October 2015) - Colapinto, Cinzia; Gavinelli, Laura; Zenga, Mariangela; Di Gregorio, Angelo
Abstract : Purpose: – The aim of this paper is to analyse why Italian small and medium enterprises (SMEs) pursue internationalization (current and future entry modes, motivations, advantages and difficulties) and how they go about it, with reference to four key areas: innovation and technology, networking, environmental approach and human resource (HR) competences. Design/methodology/approach: – A questionnaire was distributed to 792 enterprises with a response rate of 24.37 per cent. Data were collected using the computer assisted web interviewing (CAWI) method and processed with Rasch analysis, Principal Components Analysis and Cluster analysis methods. Findings: – The paper presents the results of a quantitative research on SMEs located in the Province of Monza and Brianza – one of the most productive territories in Italy. Four different clusters emerged with specific approaches. Briefly, this paper points out that: innovation is mostly linked to the product and is incremental; HR and their competences are crucial for facing complex markets; the green issue is not dominant (it is considered only for saving energy and reducing cost production); and networking is not a key issue (except informal relations, contractual agreements and strategic alliances). Research limitations/implications: – The research could be extended: through a longitudinal survey on the same sample; by covering different territories on the same topics. The cluster analysis identifies potential guidelines for entrepreneurial behaviour in respect to key factors for exiting from the economic and financial crisis: innovation and technology, formal and informal networks, the "green" approach, HR training. Originality/value: – This paper presents a new interdisciplinary approach that may work beyond country boundaries, providing a new basis to the debate on the internationalization of SMEs.